A Novel Retro-Inverso Peptide Inhibitor Reverses Angiotensin Receptor Autoantibody-Induced Hypertension in the Rabbit - Li, Hongliang (Hypertension, 2015)
Activating autoantibodies to the angiotensin II type 1 receptor (AT1R) have been implicated in hypertensive disorders. We investigated whether AT1R antibodies produced in immunized rabbits will activate AT1R and contribute to hypertension by a direct contractile effect on the vasculature; and if they can be blocked by a novel decoy peptide. A multiple antigenic peptide containing the AT1R epitope AFHYESQ, which is the receptor binding epitope of AT1R-activating autoantibodies, was used to immunize 6 rabbits. AT1R antibody activity was analyzed in AT1R-transfected cells, and their contractile effects were assayed using isolated perfused rat cremaster resistance arterioles. A retro-inverso D-amino acid (RID) epitope-mimetic peptide was tested for AT1R antibody inhibition in vitro and in vivo. All immunized animals produced high AT1R antibody titers and developed elevated blood pressure. No changes in measured blood chemistry values were observed after immunization. Rabbit anti-AT1R sera induced significant AT1R activation in transfected cells and vasoconstriction in the arteriole assay, both of which were blocked by losartan and the RID peptide. A single intravenous bolus injection of the RID peptide (1 mg/kg) into immunized rabbits dropped the mean arterial pressure from 122±11 mmHg to 82±6 mmHg. Rabbit anti-AT1R sera partially suppressed angiotensin II-induced contraction of isolated rat cremaster arterioles, and the pressor response to angiotensin II infusion was attenuated in immunized animals. In conclusion, AT1R-activating autoantibodies and the RID peptide respectively have important etiological and therapeutic implications in hypertensive subjects who harbor these autoantibodies.